Paths to Peace: Surviving Trauma as Told by Survivors. (July 2021) - Praetorius, Regina T.; Twis, Mary; Rivedal, Joshua; Moore, Danielle
Most people will experience at least one traumatic event in their lifetime. Considering outcomes such as posttraumatic stress disorder, the question emerges as to what helps people thrive and find peace posttrauma. The purpose of this qualitative study was to identify the essence of healing for individuals who have survived and thrived in the face of trauma. The content analysis of previously written accounts of healing revealed two major themes: a passageway of trauma and suffering within that passageway. Subthemes for these provide greater insight into two main approaches to assisting a person through their trauma: increasing social support and helping them restore the experience through narrative therapy.